Weighed Down by Stigma: How Weight‐Based Social Identity Threat Contributes to Weight Gain and Poor Health. Issue 6 (June 2015) - Hunger, Jeffrey M.; Major, Brenda; Blodorn, Alison; Miller, Carol T.
Abstract Weight stigma is pervasive, and a number of scholars argue that this profound stigma contributes to the negative effects of weight on psychological and physical health. Some lay individuals and health professionals assume that stigmatizing weight can actually motivate healthier behaviors and promote weight loss. However, as we review, weight stigma is consistently associated with poorer mental and physical health outcomes. In this article, we propose a social identity threat model elucidating how weight stigma contributes to weight gain and poorer mental and physical health among overweight individuals. We propose that weight‐based social identity threat increases physiological stress, undermines self‐regulation, compromises psychological health, and increases the motivation to avoid stigmatizing domains (e.g., the gym) and escape the stigma by engaging in unhealthy weight loss behaviors. Given the prevalence of overweight and obesity in the US, weight stigma thus has the potential to undermine the health and wellbeing of millions of Americans.